Supporting Employers in the Reserve Operational Forces Era Appendixes - Gates, Susan M. (RAND Corporation, 2013)
This report describes an analysis of the effects that current employment rights protections for Reserve Component members and related support programs can have on employers, given increased mobilization of the National Guard and Reserve, and makes recommendations stemming from that analysis.